The Influence Of Social Media Marketing And Brand Engagement On Brand Awareness And Brand Image (Case Study On Brownis Ingsun Products On The Account @sorgumnesia.official) - Cindy Clarissa Quenby; Nurul Azizah (UNIVED Press, 2024)
Social Media Marketing and Brand Engagement have an important role for business which has an impact on Brand Awareness and Brand Image. This research aims to identify the influence of social media marketing and brand engagement on brand awareness and brand image (case study of the brownis ingsun product on the @sorgumnesia.official account). The population in this research are Instagram followers @sorgumnesia.officia and consumers who have purchased products from Sorgumnesia, namely